Pengaruh Trend Produk Korean Wave Dan Store Atmosfer Terhadap Minat Beli Di Citra Express Padang - Puja Andriani; Fisla Wirda; Iwadiah . (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
The development of Korean culture through the Korean Wave phenomenon in Indonesia has driven increased consumer interest in Korean-inspired products. However, in practice, not all retail businesses adopting this concept are able to consistently maintain consumer purchasing interest. This also presents a challenge for Citra Express Padang, which must ensure that its product trend strategy and store atmosphere truly influence customers' purchasing decisions. This study aims to analyze and determine the extent of the influence of the Korean Wave product trend and store atmosphere on consumer purchasing interest at Citra Express Padang, both partially and simultaneously. This study used a quantitative approach, with a population of all consumers who have shopped at least once at Citra Express Padang. The sample size was 100 respondents, using non-probability sampling techniques, including accidental and purposive sampling. Data were collected by distributing questionnaires and then processed using the Statistical Package for the Social Sciences (SPSS 25) analysis tool through multiple linear regression tests to obtain objective results. The research results show that the Korean Wave product trend and store atmosphere simultaneously influence consumer purchase intention by 43.6%, while other factors outside this study contribute 56.4%. These findings indicate that Citra Express needs to increase product innovation and strengthen store atmosphere elements to maximize purchase intention in the future.